Design of functionally graded Ti–Al alloy with adjustable mechanical properties: a molecular dynamics insights - Yue Gao; Quan Xie; Tinghong Gao; Wensheng Yang; Qian Chen; Zean Tian; Lianxin Li; Yongchao Liang; Bei Wang (Journal of Materials Research and Technology, 2023)
Functional gradient materials (FGMs) are a category of advanced materials that contain two (or more) different components with continuously varying compositional distributions. With the advancement in nanotechnology, FGM applications have evolved from traditional applications to complex micro- and nano-electronic and energy conversion devices. Therefore, studying the mechanical behavior of the nanostructures of different FGMs plays a crucial role in determining the feasibility of their various applications. Herein, the mechanical behavior of the shear deformation of Ti–Al FGM nano-bulks with a radial (Z-axis direction) gradient was investigated using molecular dynamics (MD) simulations. The distributions of Ti and Al in the Z-direction were obtained using the sigmoid function. The results demonstrate that the distribution function parameters are important in regulating the mechanical properties—elastic modulus and ultimate tensile strength—of Ti–Al FGMs. It gives us a new perspective on the analysis of the microstructure evolution and dislocation density of FGMs, providing theoretical support for the practical application of FGMs.